Pemberdayaan Ekonomi Keluarga Melalui Budidaya Lele dalam Galon: Solusi Ketersediaan Protein dan Peduli Lingkungan - Bambang Sri Hartono; Mohammad Rosyada; Muhammad Taufiq Abadi (Ngarsa: Journal of Dedication Based on Local Wisdom, 2026)
Kebonsari Village, Karangdadap District, Pekalongan Regency, Indonesia, faces challenges related to limited access to protein-rich foods and low environmental awareness, underscoring the need for sustainable community empowerment programs. This community service project aimed to improve protein availability through catfish farming in gallon containers, promote economic self-reliance by creating simple income-generating opportunities suitable for limited spaces, foster environmental awareness through the utilization of organic waste, and enhance community skills in aquaculture and harvest marketing. The program adopted the Participatory Action Research (PAR) approach, consisting of problem identification, planning, implementation, and reflection. Activities included FGD, training on catfish farming in gallon containers, organic waste utilization, basic marketing strategies, and continuous mentoring for 40 participants. Data were analyzed using descriptive, comparative, and qualitative methods. The results showed a 54% increase in participants' knowledge (from 27% to 81%). A total of 92% of participants successfully cultivated catfish, with survival rates ranging from 70% to 85%; 80% achieved market-size harvests; and 70% expressed interest in expanding the activity into a small-scale business. The use of organic waste as fish feed increased to 76%, resulting in 25%–40% savings in feed costs. These findings demonstrate that catfish farming in gallon containers is an effective community empowerment model for simultaneously improving nutrition, economic resilience, and environmental awareness, with strong potential for replication in communities with similar characteristics. Keywords: Family Economic Empowerment; Catfish Farming in Gallon Containers; Protein Availability. Abstrak: Desa Kebonsari, Kecamatan Karangdadap, Kabupaten Pekalongan, menghadapi rendahnya ketersediaan pangan berprotein dan rendahnya kesadaran lingkungan, sehingga diperlukan program pemberdayaan masyarakat yang berkelanjutan. Kegiatan pengabdian ini bertujuan untuk meningkatkan ketersediaan protein melalui budidaya lele dalam galon, mendorong kemandirian ekonomi dengan menyediakan peluang usaha sederhana yang dapat dilakukan di lahan sempit, menumbuhkan kesadaran lingkungan melalui pemanfaatan limbah organik, serta meningkatkan keterampilan warga dalam teknik budidaya dan pemasaran hasil panen. Metode pengabdian menggunakan Participatory PAR melalui tahapan identifikasi masalah, perencanaan, pelaksanaan, dan refleksi. Kegiatan meliputi FGD, pelatihan budidaya lele dalam galon, pemanfaatan limbah organik, strategi pemasaran, serta pendampingan bagi 40 peserta. Data dianalisis secara deskriptif, komparatif, dan kualitatif. Hasil menunjukkan bahwa pengetahuan peserta meningkat sebesar 54% (dari 27% menjadi 81%). Sebanyak 92% berhasil membudidayakan lele dengan tingkat kelangsungan hidup 70–85%, 80% mencapai ukuran panen, dan 70% berminat mengembangkan usaha. Pemanfaatan limbah organik sebagai pakan meningkat menjadi 76% dengan efisiensi biaya 25–40%. Model ini efektif dalam meningkatkan gizi, ekonomi, dan kepedulian terhadap lingkungan serta layak direplikasi. Kata kunci: Pemberdayaan Ekonomi Keluarga, Budidaya Lele dalam Galon, Solusi Ketersediaan Protein